Molecular Diagnosis of Kingella kingae Pericarditis by Amplification and Sequencing of the 16S rRNA Gene - Matta, Matta (American Society for Microbiology, 2007)
Kingella kingae is a fastidious gram-negative bacillus that is considered an emerging pathogen in pediatric settings but remains less common in adults. Here we describe a case of pericarditis in an immunocompetent adult host. The microorganism was identified directly from the clinical sample by molecular techniques, i.e., 16S rRNA gene amplification and sequencing.